Preparation Titanium Dioxide Combined Hydrophobic Polymer with Photocatalytic Self-Cleaning Properties - Sayekti Wahyuningsih; Rochmad E. Cahyono; Fitri N. Aini (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
Titanium dioxide (TiO2) and hydrophobic of TiO2/PDMS (PDMS = polydimethylsiloxane) have been prepared as photocatalytic self-cleaning materials. Synthesis of TiO2 was carried out using the sol-gel method with titanium(IV) isopropoxide (TTIP) as a precursor and acetic acid as a solvent at a temperature of about 10–15 °C, while the synthesis of hydrophobic of TiO2/PDMS composites was carried out by a sonication method under ethanol solution. The results of XRD analysis of synthesized TiO2 showed that TiO2 was anatase phase. The glass-coated TiO2/PDMS were prepared by dip-coating under an ultrasonication bath. TiO2/PDMS composites at a ratio of TiO2/PDMS (1) on the glass plate showed hydrophobic properties, as evidenced by the contact angle of 104° before irradiation and the contact angle of 99.7° after irradiation. The synthesized titanium dioxide has irregular spherical morphology. The increase in PDMS content was correlated with an increase in the roughness of TiO2. PDMS not only acts as low surface energy but also binds TiO2. The hydrophobic behavior of PDMS creates TiO2/PDMS repel each other, gain irregular agglomeration structures. Beside having optimum contact angle, glass-coated TiO2/PDMS (1) is the best composition for degradation of methylene blue in 69.68% for 20 minutes irradiation. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).